2017
DOI: 10.4269/ajtmh.17-0129
|View full text |Cite
|
Sign up to set email alerts
|

Population Movement as a Risk Factor for Malaria Infection in High-Altitude Villages of Tahtay–Maychew District, Tigray, Northern Ethiopia: A Case–Control Study

Abstract: Key goal and targets of the Ethiopia National Malaria Control Program are to achieve malaria elimination within specific geographical areas with historically low malaria transmission and to reach near-zero malaria transmission in the remaining malarious areas by 2020. However, back and forth population movement between high-transmission and low-transmission area imposes challenge on the success of national malaria control programs. Therefore, examining the effect of human movement and identification of at-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…All studies used either a case-control or cross-sectional design, but some differed in their case ascertainment methods and geographical/ temporal criteria for defining the travel variable. Most of the studies recruited patients diagnosed with malaria at particular health facilities for inclusion; seven studies surveyed randomly selected households across the study area; one study in Botswana 11 looked at all inhabitants of the study site, and one study in Ethiopia 19 looked at all current residents of the seven villages selected. Two studies used data collected from active surveillance systems (Tanzania 31 and Swaziland 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies used either a case-control or cross-sectional design, but some differed in their case ascertainment methods and geographical/ temporal criteria for defining the travel variable. Most of the studies recruited patients diagnosed with malaria at particular health facilities for inclusion; seven studies surveyed randomly selected households across the study area; one study in Botswana 11 looked at all inhabitants of the study site, and one study in Ethiopia 19 looked at all current residents of the seven villages selected. Two studies used data collected from active surveillance systems (Tanzania 31 and Swaziland 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…30 Previous studies on this topic have often been health facility based, using a case–control design to compare travel exposure and infection among patients. 19 24 That design, although providing insights into the role of travel on individual malaria infection, does not lend itself to estimates of the relative importance of importation to current malaria prevalence and has often been limited in its ability to consider differences in risk due to characteristics of travel. Not all travel impose a substantial risk to malaria infection, and consideration of risk at trip destination is important; movement between areas with little transmission or during times with low vector activity is unlikely to have a substantial impact on travelers and onward transmission compared with travel to highly endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,18 Within sub-Saharan Africa, previous studies have provided empirical evidence demonstrating a general association between travel and individual parasitemia, especially among individuals returning to lower prevalence areas. [19][20][21][22][23][24] Not all types of travel pose the same risk for infection nor does travel necessarily translate into a significant threat to lowprevalence areas. An individual's duration and frequency of travel, risk while traveling, and risk management behaviors contribute to the probability of acquiring parasites.…”
Section: Introductionmentioning
confidence: 99%
“…The odds of malaria among Bioko Island residents who travelled was signi cantly higher than in non-travellers, suggesting that imported malaria cases contributed to the sustained transmission of malaria on the island [19]. Similarly, a study in northern Ethiopia found that travel from high-altitude (low transmission) villages to other areas within the previous month was associated with increased odds of malaria [31]. This evidence suggests that travel within Africa is a risk factor for malaria infection.…”
Section: Discussionmentioning
confidence: 97%
“…Other factors that were not associated with LLIN use during travel included time to bed, gender of the participant, and age at the time of travel. Travel has been identi ed as a risk factor for malaria across Africa [11,15,19,30,31]. In Uganda, a study conducted at three sites of varied malaria transmission demonstrated that the incidence of malaria in travellers was over three times higher in the 60 days after overnight travel compared to the 60 days before travelling [16].…”
Section: Discussionmentioning
confidence: 99%